New pathways and metabolic engineering strategies for microbial synthesis of diols - Cen, Xuecong; Dong, Yang; Liu, Dehua; Chen, Zhen (Current opinion in biotechnology, 2022)
Diols are important bulk chemicals that are widely used in polymer, cosmetics, fuel, food, and pharmaceutical industries. The development of bioprocess to produce diols from renewable feedstocks has gained much interest in recent years and is contributing to reducing the carbon footprint of the chemical industry. Although bioproduction of some natural diols such as 1,3-propanediol and 2,3-butanediol has been commercialized, microbial production of most other diols is still challenging due to the lack of natural biosynthetic pathways. This review describes the recent efforts in the development of novel synthetic pathways and metabolic engineering strategies for the biological production of C2∼C5 diols. We also discussed the main challenges and future perspectives for the microbial processes toward industrial application. [Display omitted] ●Advances in the biological production of important C2–C5 diols are reviewed.●Recent advances in synthetic biology enable the construction of non-natural pathways.●Systems' metabolic engineering accelerates the development of diols' bioproduction.